Effect of Electroacupuncture on Rat Ischemic Brain Injury: Importance of Stimulation Duration. (13th May 2013) - Zhou, Fei; Guo, Jingchun; Cheng, Jieshi; Wu, Gencheng; Xia, Ying
Abstract : We explored the optimal duration of electroacupuncture (EA) stimulation for protecting the brain against ischemic injury. The experiments were carried out in rats exposed to right middle cerebral artery occlusion (MCAO) for 60 min followed by 24-hr reperfusion. EA was delivered to "Shuigou" (Du 26) and "Baihui" (Du 20) acupoints with sparse-dense wave (5/20 Hz) at 1.0 mA for 5, 15, 30, and 45 min, respectively. The results showed that 30 min EA, starting at 5 minutes after the onset of MCAO (EA during MCAO) or 5 minutes after reperfusion (EA after MCAO), significantly reduced ischemic infarct volume, attenuated neurological deficits, and decreased death rate with a larger reduction of the ischemic infarction in the former group. Also in the group of EA during MCAO, this protective benefit was positively proportional to the increase in the period of stimulation, that is, increased protection in response to EA from 5- to 30-min stimulation. In all groups, EA induced a significant increase in cerebral blood flow and promoted blood flow recovery after reperfusion, and both blood flow volume and blood cell velocity returned to the preischemia level in a short period of time. Surprisingly, EA for 45 min did not show reduction in the neurological deficits or the infarct volume and instead demonstrated an increase in death rate in this group. Although EA for 45 min still increased the blood flow during MCAO, it led to a worsening of perfusion after reperfusion compared to the group subjected only to ischemia. The neuroprotection induced by an "optimal" period (30 min) of EA was completely blocked by Naltrindole, a δ -opioid receptor (DOR) antagonist (10 mg/kg, i.v.). These findings suggest that earlier EA stimulation leads to better outcomes, and that EA-induced neuroprotection against ischemia depends on an optimal EA-duration via multiple pathways including DOR signaling, while "over-length" stimulation exacerbates the ischemic injury.